A randomized control trial comparing vaginal and laparoscopically-assisted vaginal hysterectomy in the absence of uterine prolapse in a South African tertiary institution. (December 2021) - Chrysostomou, Andreas; Djokovic, Dusan; Libhaber, Elena; Edridge, William; Kawonga, Mary; van Herendael, Bruno J.
Highlights: Vaginal hysterectomy for non-prolapsed uterus is feasible and safe. Vaginal hysterectomy is faster and less costly than laparoscopically-assisted vaginal hysterectomy. Where possible, vaginal hysterectomy should be the preferred route for benign uterine pathology. Abstract: Objectives: The primary objectives of this study were to estimate blood loss, operation time and cost differences in patients undergoing vaginal hysterectomy (VH) versus laparoscopically-assisted vaginal hysterectomy (LAVH). The secondary objectives were to determine differences in hospital stay, need for postoperative analgesia, intra- and immediate post-operative complications, and the rate of conversion to laparotomy. VH was hypothesized to be the preferred route for hysterectomy for benign uterine conditions. Study Design: A randomized control study was undertaken at the Department of Obstetrics and Gynaecology of the Charlotte Maxeke Johannesburg Academic Hospital and included the women admitted between January 2017 and December 2019 for hysterectomy due to benign conditions, meeting the inclusion criteria (vaginally accessible uterus, estimated uterine size ≤ 12 weeks of gestation or ≤ 280 g on ultrasound examination and pathology confined to the uterus). Surgical procedures were performed by the residents in training under the supervision of specialists with large experience. The patient demographic characteristics, uterine weight, operative time, estimated blood loss(expressed as the difference between preoperative and postoperative day one serum haemoglobin), direct surgery-associated costs, intra- and immediate post-operative complications and the length of hospital stay were recorded and comparatively analysed among patients randomly placed in VH and LAVH group. Results: A total of 227 women were included (151 patients underwent VH and 76 LAVH, upon 2:1 randomization, performed on this way to reflect the previous pattern of operating of the unit). The patients were matched with respect to age, parity and body mass index. No significant differences between two groups were found in mean uterine weight and also in mean serum haemoglobin shift, intra- and immediate post-operative complications, and convalescence period duration. There were statistically significant differences in operating time and in cost between the two procedures. On average, LAVH took longer than VH to be performed (62.8 ± 9.3 vs 29.9 ± 6.6 min, p < 0.0001) and it was more costly, mainly due to the longer operating time and required disposables. An amount of 15698.20 South African Rand (ZAR) or 1145.85 United States Dollar (USD) more were needed to perform LAVH in comparison to VH. All VHs and LAVHs were successfully accomplished without major complications or conversation to laparotomy. Conclusion: Our data indicate that VH is a feasible and safe alternative for a large group of women with benign pathology and non-prolapsed uteri, being a faster and less costly procedure than LAVH.